2019
DOI: 10.1101/691824
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuous Endoglin (CD105) Overexpression Disrupts Angiogenesis and Facilitates Tumor Cell Metastasis

Abstract: Running Title: High CD105 levels promote vessel instability and metastasis ABSTRACTAngiogenesis is a complex process essential for tumor growth. For this reason, high levels of pro-angiogenic molecules, such as endoglin (CD105), are supposed to be related to greater tumor growth that lead to a poor cancer prognosis. However, we demonstrate here that defects in angiogenesis that can be attributed to high levels of endoglin, lead to development and worsening of cancer disease. Steady endoglin overexpression disr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Tumor angiogenesis plays a crucial role in the initiation of tumors, and their progression, invasion, and metastasis ( 6 , 7 ). Antiangiogenic therapies represent a promising anticancer treatment strategy, already extensively used for the treatment of solid tumors, aiming to inhibit tumor angiogenesis by targeting the key signaling pathways in which it is implicated ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor angiogenesis plays a crucial role in the initiation of tumors, and their progression, invasion, and metastasis ( 6 , 7 ). Antiangiogenic therapies represent a promising anticancer treatment strategy, already extensively used for the treatment of solid tumors, aiming to inhibit tumor angiogenesis by targeting the key signaling pathways in which it is implicated ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first one, CD105 is a well-known receptor for TGF-β [19]. It has been widely researched in the topic of cancer, especially tumour angiogenesis [20]. However, while it is also expressed in stem cells, its role is currently not fully elucidates, as it was demonstrated that its expression has no effect on differentiation ability and does not allow to distinguish a population of MSCs able to progress towards a chondrogenic lineage fate [21].…”
Section: Discussionmentioning
confidence: 99%
“…This autosomal dominant disorder, characterized by abnormal blood vessel formation, illustrates how mutations in endoglin result in clinical manifestations such as epistaxis and arteriovenous malformations (AVMs) in critical organs, posing serious health risks. [4][5][6][7][8][9] Although virtually all endothelial cells in HHT patients suffer from haploinsufficiency, AVMs are rare, suggesting the occurrence of "additional hits" for their manifestation, such as somatic mutation, mechanical trauma and/or inflammation. [10][11][12] This complexity is further illustrated by studies correlating AVMs with decreased endoglin expression and abnormal responses to angiogenic stimuli such as VEGF.…”
Section: Introductionmentioning
confidence: 99%